Impingement of the ankle joint—a systematic review on the expected outcome - Maximilian A. Hamberger; Maximilian M. Saller; Wolfgang Böcker; Hans Polzer; Sebastian F. Baumbach (BMC Musculoskeletal Disorders)
Abstract Background Impingement syndrome of the ankle is a multifaceted condition. It can affect all regions within the ankle joint and can be caused either by bony prominences or soft tissue. Exact numbers on the incidences are missing, prevalence rates up to 60% are estimated in certain risk groups. Previous systematic reviews have focused on specific anterior or posterior ankle impingements. Still, a comprehensive overview over impingement syndromes of the ankle and the outcome to be expected is missing. This systematic review aims at giving a comprehensive overview on studies reporting on the outcome of any kind of ankle impingement. Methods A systematic review was conducted, based on a thorough search strategy in four databases following the PRISMA guidelines. Included were all studies reporting on the outcome for any sort of ankle impingement. Assessed data were the level of evidence, study details, general demographics, injury details, surgical treatment, postoperative treatment protocol, follow-up time, complications, and outcome. Analyzed were comparable outcome parameters presented in at least three studies. Results Out of 3083 screened abstracts, 85 studies were eligible for qualitative and 37 studies for quantitative analysis. The AOFAS was assessed by 21 studies, with significant postoperative improvement in all studies. In all but two studies, mean postoperative AOFAS scores above 80 points were achieved. The VAS pain on a 10-point Likert scale was reported in 12 studies and improved in all. Return to sports was reported as a percentage/duration in 17/14 studies. At least 70% of patients returned to sports in all but one study. Conclusions This study is the first to provide a comprehensive overview over the expected outcomes following surgical treatment of any ankle impingement syndrome. The great heterogeneity of the studies did not allow a pathology-specific comparison. Surgery apparently improves the symptoms considerably, but the outcome varies between the different types of impingements, with a posterior os trigonum impingement resulting in the most favorable outcomes. Trial registration The study was a-priori registered at Prospero (#CRD42022354685) on August 19th, 2022. Level of evidence Level 1 Systematic Review.